On the Political Substitutability between Tariffs and Subsidies - Daniel Brou; Michele Ruta (Swiss Journal of Economics and Statistics, 2009)
This paper provides a simple model that highlights the political substitutability between import tariffs and production subsidies.1 When taxes are distortionary, political pressures by domestic interest groups representing the import competing sector induce the government to set inefficiently high tariffs and subsidies. If the government commits the tariff to a lower level - for instance by signing a binding commitment in a trade agreement - interest groups demand (and in the political equilibrium obtain) a larger production subsidy. This political substitutability between tariffs and subsidies is shown to reduce social welfare.
Keywords: F13; D72; F55; H25; 330; tariffs; subsidies; lobbying; trade agreements